Examining Construct Congruence for Psychometric Tests: A Note on an Extension to Binary Items and Nesting Effects. (February 2018) - Raykov, Tenko; Marcoulides, George A.; Dimitrov, Dimiter M.; Li, Tatyana
This article extends the procedure outlined in the article by Raykov, Marcoulides, and Tong for testing congruence of latent constructs to the setting of binary items and clustering effects. In this widely used setting in contemporary educational and psychological research, the method can be used to examine if two or more homogeneous multicomponent instruments with distinct components measure the same construct. The approach is useful in scale construction and development research as well as in construct validation investigations. The discussed method is illustrated with data from a scholastic aptitude assessment study.